Application of Superman Songs In the Pop Rock Genre Goes to Reggae with Ensemble Format at SMAN 3 Padangpanjang - rizki, azkia ghaniya; Yonhendri, Yonhendri -; Emridawati, Emridawati -; Awerman, Awerman -; Anggara, Rama (Institut Seni Indonesia Padangpanjang, 2025)
The research entitled